Developing a foundation for targeted NOx photodegradation: integrating scalable carbon nanotube synthesis and fundamental photocatalysis mechanism analysis - Smith, Morgen L. (My University, 2026)
Nitrogen oxides (NOx) pose a persistent threat to global respiratory health and environmental stability. Photocatalytic degradation is extensively studied as a low-cost, low-energy method for NOx abatement, yet conventional mitigation strategies often fail to address the evolution of NO₂ – a more toxic pollutant – under real-world, high-humidity conditions. Titanium dioxide (TiO₂) is a widely used photocatalyst – both for NOx photocatalytic degradation and other environmental remediation applications – and remains a "gold standard" for photocatalytic atmospheric remediation. However, its efficacy in NOx abatement is fundamentally limited by rapid charge recombination and the unintended release of toxic NO₂ intermediates as relative humidity (RH) approaches realistic atmospheric levels. This research is focused on developing the understanding required to address these critical gaps by investigating advanced TiO₂-nanocarbon hybrids – utilizing both multi-walled carbon nanotubes (MWCNTs) and Ti₂CTx MXenes – to fundamentally redirect photocatalytic degradation mechanistic pathways and isolate active charge species. The creation of Schottky barriers and heterojunctions in TiO₂-based hybrids will require the coupling of carbon nanotubes with distinct electronic properties. By combining these mechanistic insights with a scalable, autonomous synthesis framework for rapidly investigating the experimental space for floating-catalyst chemical vapor deposition growth of single-walled carbon nanotubes (SWCNTs) for targeting specific properties, this work establishes a comprehensive roadmap for the rational design of environmentally adaptive catalysts capable of sustained performance in diverse and complex atmospheric conditions. Through a systematic matrix of experiments this study isolates photocatalytic mechanistic pathways by employing (1) hole (h⁺) scavengers, (2) hydroxyl radical (HO ̇ ) scavengers (3) controlled humidity levels (0% RH, 20% RH, or 50% RH), (4) carrier gas chemistry (air or N₂), and (5) NOx pollutant gas (NO or NO₂). This study parses the distinct roles of h⁺, HO ̇ , H₂O, and superoxide radicals (O ₂ ̇ ⁻). These findings reveal a significant divergence in mechanistic pathways governed by the choice of nanocarbon. By shifting the reaction towards a superoxide-dominated pathway, TiO₂ MWCNT hybrids overcome the performance barriers of pristine TiO₂. Within this hybrid architecture, MWCNTs provide a critical functionality by physisorbing moisture to stabilize superoxide radicals and shield the TiO₂ surface from moisture-induced toxification. This allows TiO₂ MWCNT to maintain high performance in humid conditions without the unintended toxification through NO₂ formation. TiO₂ Ti₂CTx MXene hybrids rely primarily on the hydroxyl pathway. The integration of these nanocarbons create Schottky barriers that physically separate superoxide and hydroxyl reaction sites, thereby inhibiting side reactions that lead to intermediate NO2 release. While single-walled carbon nanotubes (SWCNTs) offer superior interfacial contact and tunable electronic properties, their targeted synthesis for scalable photocatalytic applications remains a significant challenge. Therefore, this investigation utilizes MWCNTs to establish foundational NOx degradation mechanisms while simultaneously advancing SWCNT growth through an automated research floating-catalyst chemical vapor deposition reactor (FC2-ARES) to rapidly investigate a large synthesis space to achieve optimal growth. By promoting iron (Fe) catalysts with ruthenium (Ru), this study achieves enhanced thermal resilience, enabling stable SWCNT growth at temperatures exceeding 1000 ◦C – a threshold where pure Fe catalysts fail in this system. This synthesis space was mapped using the ARES OS 2.0 system, identifying low-Ru loadings as the most effective for high-quality carbon sequestration and optimal growth metrics. By deconstructing these mechanisms, this work establishes a foundational framework for the rational design of environmentally adaptive photocatalysts tailored to local humidity and NOx composition, providing a robust methodology for large-scale environmental remediation.
Keywords: Photocatalysis; Carbon nanotubes; Nitrogen oxides